Pengaruh Profitabilitas, Leverage dan Biaya Penelitian dan Pengembangan terhadap Nilai Perusahaan - Sabna Aprila Maharani; Elen Puspitasari (Jurnal Akuntansi dan Pajak, 2022)
This study aims to analyze and examine the effect of probability, leverage and research and development costs on firm value. This reaserch is a type of quantitative research using secondary data from manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique in this research is purposive sampling. The sample in the study obtained a total of 80 samples, in terms of the method of determining the criteria that have been determined. The data analysis method used multiple linear regression. The results of this study explain that profitability and research and development costs have a positive effect on firm value, while leverage has no effect on firm value.